2023
DOI: 10.3390/fire6050177
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical Simulation on the Smoke Prevention Performance of Air Curtains in an Island-Type Subway Station

Abstract: Subway fires are a major threat to the safe and smooth operation of subway stations. In this paper, an island-type subway station was taken as an example to conduct a series of numerical simulations using Fire Dynamics Simulator (FDS). The temperature, visibility, and CO concentration in the subway station were analysed under different thicknesses and jet velocities of the air curtains. The smoke-prevention performance of the air curtains in the subway station was investigated. As the thickness and jet velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the original publication [1], funding from Central South University, NO. 2023ZZTS0951, to Xu Yan was not included.…”
Section: Missing Fundingmentioning
confidence: 99%
“…In the original publication [1], funding from Central South University, NO. 2023ZZTS0951, to Xu Yan was not included.…”
Section: Missing Fundingmentioning
confidence: 99%
“…analyzed the conditions of an emergency ventilation system consisting of air curtains and exhaust fans to manage heat and toxicity in various fire scenarios [12]. Yan et al revealed that the minimum thickness for sealing effectiveness is 0.3 m and that the jet velocity should be at least 2 m/s, depending on the thickness and spray velocity of the air curtain [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, they considered only hot-gas temperature. Hofmann and Muehlnikel [18] conducted a fire investigation with Fire Dynamics Simulator (FDS) [19][20][21], a CFD model widely adopted for simulating fire dynamics, to reconstruct the spread of a fire in a five-storey building that had resulted in two fatalities. They assumed the fire location and power prior to the CFD simulation, which revealed that the non-compliance of several building products was responsible for the fatalities.…”
Section: Introductionmentioning
confidence: 99%